Impact of Weather and Climate Change in the Area of Cultivation and Cropping Pattern in Villupuram – A Micro Analysis in Machine learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Climate change and agricultural production are also interrelated. So in the article, we will look at the Villupuram district's studies in agrarian production-related to climate change. Agriculture is considering to be the lifeblood of Tamil Nadu. The majority of the people in Villupuram are engaged in agriculture. Villupuram district is one of the agriculture districts in which 75% of the population is involved in agriculture.  There are 5.68 farm families from Lakh in the Vilupuram District. Seventy-five percent are marginal farmers, 16 percent are small farmers, and 9 percent are large farmers. Big farmers account for 42 percent, 34 percent higher than the state average. The district of Vilupuram shares a unique position in developing state food grains. The section of Vilupuram ranked first in food grain production from 2013-14 to 2017-18. Villupuram accounts for more than 10 percent of the state's food production per year. In this article, I have taken two Machine learning algorithms. Taking ten years of data, I can predict that the current rainfall will be 70% and the temperature will be 20%, and in the future, the precipitation will decrease by 30%, and the temperature will increase by 60%. I want to point out that the amount of agricultural production related to weather is presently 30% and that the show may decrease by 10 to 20%. I will explain with Random Forest and Logistic Regression that Random Forest works very well and gives good results.